Michael D. Wise and Jennifer Jensen Wallach (eds.) (2017), "The Routledge History of American Foodways", New York, Routledge Taylor& Francis Group [2016] - Castilho, Maria Teresa (Cadernos de Literatura Comparada, 2019)
.